FORMATION OF AN EFFICIENT COMPLEX SUPPLY SYSTEM ECONOMIC SECURITY OF THE ENTERPRISE - BAKAY, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article discusses important issues regarding the creation of a system of economic security of the enterprise, as there is no clear position regarding its necessity. A model of the formation of an effective system of comprehensive provision of economic security of the enterprise based on the implementation of specific actions that determine its mission and goals is presented. It is necessary to ensure the implementation of the specified algorithm of actions and take preventive measures to achieve economic security, and to build in accordance with the implemented policy and the formation of a strategy for its economic security. In this case, the strategy is considered as a long-term approach to achieve the company's goals. In order to counter threats to the economic security of the enterprise and ensure its stable functioning, it is necessary not only to create a comprehensive protection system, but also to ensure its rational functioning for the future.Depending on the state of the enterprise and the influence of external and internal factors on it, a set of measures is proposed to strengthen the economic security of the enterprise in terms of a separate functional component. It was found that all directions for each separate functional component of the enterprise's economic security provide an opportunity to strengthen the enterprise's economic security as a whole. The result of ensuring the economic security of the enterprise should be the stability of the functioning of the enterprise, the dynamism of its development, the efficiency of financial and economic activity and the personal safety of employees working at this enterprise.The use of a scientific and methodical approach when building an effective system of comprehensive provision of economic security of the enterprise makes it possible to take into account all possible threats, while all the means of protection used, the developed measures must be interconnected. The creation of such a system allows you to play a key role in ensuring sustainable functioning and the most effective development of the enterprise on the basis of a developed and implemented set of measures.
Keywords: economic security; economic security system; principles; measures; strategy; threats; functional components; levels of economic security